Process for the vulcanization of a medical halogenated butyl rubber needle-resistant stopper

CN122878679APending Publication Date: 2026-10-09HUBEI LIKANG MEDICAL MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611213583.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-11
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0004]本发明的目的是针对现有技术中医用卤化丁基橡胶塞在多次针刺过程中容易产生胶屑脱落、穿刺后自密封性能不足、常规补强填料与橡胶基体相容性差导致界面结合力弱,以及耐针刺性能和穿刺密封性能难以同时兼顾等问题,提供一种复合功能填料分散均匀、填料与橡胶基体形成化学界面键合、耐针刺和穿刺后自密封性能优良的一种医用耐针刺卤化丁基橡胶塞的硫化制备工艺

Benefits of technology

[0027]1.本发明中复合功能填料表面接枝的巯基在硫化过程中与卤化丁基橡胶发生交联反应,形成化学界面键合,填料与橡胶基体之间的结合强度较高,针刺时填料不易从橡胶中脱出,穿刺落屑问题得到缓解。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122878679A_ABST
    Figure CN122878679A_ABST
Patent Text Reader

Abstract

The application discloses a medical needle-penetration-resistant halogenated butyl rubber plug and a vulcanization preparation process thereof, and relates to the technical field of medical rubber plugs. The rubber plug comprises the following components in mass parts: halogenated butyl rubber 100 parts, polyisobutylene 5-20 parts, polyvinyl chloride 5-15 parts, composite functional filler 10-30 parts, vulcanizing agent 2-5 parts, accelerator 0.5-2 parts, and active agent 1-3 parts. The composite functional filler has a core-shell structure, with polyurethane elastomer microspheres as the core, a silica shell layer coated outside the core, and gamma-mercaptopropyl trimethoxysilane bonded on the surface of the shell layer. In the vulcanization process, the mercapto groups on the surface of the filler and the halogenated butyl rubber are crosslinked to form chemical interface bonding. The rubber plug is chemically combined with the rubber matrix through the composite functional filler, and the polyurethane inner core is elastically recovered, so that less rubber crumbs are shed after multiple needle penetrations, the puncture hole is closed faster, and the self-sealing performance is better.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of medical rubber stopper technology, specifically to a vulcanization preparation process for a medical needle-puncture resistant halogenated butyl rubber stopper. Background Technology

[0002] In the healthcare industry, halogenated butyl rubber stoppers are increasingly replacing natural rubber stoppers. However, during clinical infusion and injection procedures, puncture debris is a prominent issue with butyl rubber stoppers. When the needle punctures the stopper, the shearing action between the needle and the rubber can easily cause localized rubber detachment, producing visible rubber debris particles. If these debris enters the medication solution, it can contaminate the drug and directly affect medication safety. Studies have shown that puncture debris is related to factors such as the stopper formulation, mixing process, and needle structure, with the stopper's own performance being a crucial element. The ability of the stopper to maintain a tight seal after multiple punctures is also an issue that cannot be ignored.

[0003] Vaccine vials, powder injections, and other drug packaging often require multiple aspirations for dispensing during use. If the puncture hole does not close tightly, external microorganisms or liquids may seep into the vial, leading to drug contamination or leakage. Existing standards have clear requirements for the self-sealing properties of rubber stoppers, and the testing methods are relatively mature. However, in actual production and use, simultaneously achieving high puncture resistance and good sealing after puncture remains challenging. If the reinforcing filler in the formulation has poor compatibility with the rubber matrix, resulting in weak interfacial bonding, the puncture force tends to concentrate at the weak interface between the filler and the rubber, exacerbating rubber debris shedding. Therefore, finding a balance between rubber stopper formulation design and filler modification to reduce debris shedding while maintaining a seal under repeated puncture conditions is a direction that requires continuous improvement in this field. Summary of the Invention

[0004] The purpose of this invention is to address the problems in existing medical halogenated butyl rubber stoppers, such as easy shedding of rubber debris during repeated needle punctures, insufficient self-sealing performance after puncture, poor compatibility between conventional reinforcing fillers and the rubber matrix leading to weak interfacial bonding, and difficulty in simultaneously achieving needle resistance and puncture sealing performance. This invention provides a vulcanization preparation process for a medical needle-resistant halogenated butyl rubber stopper that features uniform dispersion of composite functional fillers, chemical interfacial bonding between the filler and the rubber matrix, and excellent needle resistance and self-sealing performance after puncture.

[0005] To achieve the above objectives, the technical solution adopted by the present invention is: a medical needle-puncture resistant halogenated butyl rubber stopper, which is composed of the following components in parts by weight: 100 parts of halogenated butyl rubber, 5-20 parts of polyisobutylene, 5-15 parts of polyvinyl chloride, 10-30 parts of composite functional filler, 2-5 parts of vulcanizing agent, 0.5-2 parts of accelerator, and 1-3 parts of activator.

[0006] Furthermore, the composite functional filler has a core-shell structure, with polyurethane elastomer microspheres as the core. The polyurethane elastomer microspheres are made by reacting polypropylene glycol, isophorone diisocyanate, dimethylolpropionic acid, triethylamine, and ethylenediamine with a number average molecular weight of 1000-3000. The core is coated with a continuous silica shell. The surface of the silica shell is chemically bonded with γ-mercaptopropyltrimethoxysilane through silicon-oxygen bonds, and the amount of thiol grafting is 0.42-0.60 mmol / g. Moreover, the thiol consumption rate of the composite functional filler after reacting with the 1-bromobutane model is not less than 85%.

[0007] Furthermore, the composite functional filler is prepared by a multi-step reaction from the following raw materials with a number average molecular weight of 1000-3000: 100 parts of polypropylene glycol, 30-35 parts of isophorone diisocyanate, 5-10 parts of dimethylolpropionic acid, 5-10 parts of triethylamine, 1-5 parts of ethylenediamine, 25-35 parts of tetraethyl orthosilicate, 10-12 parts of γ-mercaptopropyltrimethoxysilane, 12-18 parts of ammonia water with a mass concentration of 25%-28%, 300-350 parts of anhydrous ethanol, and 80-100 parts of deionized water.

[0008] Furthermore, X-ray photoelectron spectroscopy revealed that the composite functional filler surface exhibits both S2p and Si2p signals, and after Soxhlet extraction with anhydrous ethanol for 6 hours, the S2p / Si2p peak area ratio retention rate was not less than 85%.

[0009] Furthermore, the preparation method of the composite functional filler includes the following steps:

[0010] A1. Preparation of polyurethane elastomer microspheres: Polypropylene glycol was vacuum dehydrated at 100-120℃, cooled to 60℃, and isophorone diisocyanate was added. The mixture was stirred at 75-85℃ for 2-3 hours to obtain an isocyanate-terminated prepolymer. Dimethylolpropionic acid was added, and the mixture was stirred at 75-80℃ for 1-2 hours. The temperature was then lowered to 40℃, and triethylamine was added for neutralization, with a neutralization degree of 90%-100%. The neutralized prepolymer was dispersed in deionized water under high-speed stirring at 1000-1500 rpm, and ethylenediamine was added for post-chain extension. The solid content was controlled at 20%-30% to obtain a polyurethane elastomer microsphere emulsion.

[0011] A2. Silica shell coating: Take 100 parts of the polyurethane elastomer microsphere emulsion obtained in step A1, based on the dry weight of the microspheres, and add it to a mixed solvent composed of anhydrous ethanol and deionized water in a volume ratio of 4:1. Disperse the mixture ultrasonically at a power of 200-500W, a frequency of 40kHz, and a time of 15-30min. Adjust the pH of the system to 9-10 with the ammonia water, raise the temperature to 40-50℃, and add tetraethyl orthosilicate dropwise at a rate of 0.5-1.0mL / min with stirring for 1-2h. After the addition is complete, continue stirring and reacting for 4-6h to obtain a core-shell microsphere suspension of polyurethane coated with silica.

[0012] A3. Surface grafting modification: Add γ-mercaptopropyltrimethoxysilane to the core-shell microsphere suspension obtained in step A2, stir and react at 50-60℃ for 3-5 hours, then adjust the pH of the system to 6-7 with glacial acetic acid, and continue aging for 2 hours.

[0013] A4. Post-processing: Centrifuge the product obtained in step A3 at 8000-10000 rpm for 15-20 min, discard the supernatant, wash the solid alternately with deionized water and anhydrous ethanol, vacuum dry at 60-80℃ for 12-24 h, mechanically pulverize and pass through a 300-mesh sieve to obtain the composite functional filler.

[0014] The composite functional filler can be viewed layer by layer from its structure. The polyurethane elastomer microspheres, serving as the core, possess a certain degree of flexibility and resilience, buffering the localized shear force experienced by the rubber during needle puncture. The outer silica shell covering the core is relatively hard, improving the overall rigidity of the filler and preventing excessive deformation or crushing of the polyurethane microspheres during mixing and vulcanization. γ-mercaptopropyltrimethoxysilane is chemically bonded to the surface of the silica shell, essentially attaching mercapto groups to the filler surface. During vulcanization, these mercapto groups cross-link with the halogen atoms on the butyl rubber molecular chains, forming strong chemical bonds. Thus, the filler is no longer simply physically dispersed within the rubber, but directly fixed to the rubber matrix through chemical bonds. This interfacial chemical bonding significantly enhances the bonding force between the filler and the rubber, making it less likely for the filler to be pulled out of the rubber during needle puncture, thus reducing the possibility of rubber debris shedding. Simultaneously, the elasticity of the polyurethane core helps the rubber around the needle puncture hole to rebound and close promptly, improving the sealing effect after puncture. Simply put, this filler uses a soft core and hard shell with surface chemical grafting, which not only improves dispersion but also binds the filler and rubber together through a chemical reaction.

[0015] Furthermore, the halogenated butyl rubber is chlorinated butyl rubber or brominated butyl rubber.

[0016] Furthermore, the sulfiding agent is selected from one or more of magnesium oxide and sulfur.

[0017] Furthermore, the accelerator is selected from one or more of tetramethylthiuram disulfide, zinc diethyldithiocarbamate, and 2-mercaptobenzothiazole;

[0018] The active agent is stearic acid.

[0019] A vulcanization process for preparing a medical needle-puncture-resistant halogenated butyl rubber stopper includes the following steps:

[0020] B1. The halogenated butyl rubber is plasticized in a thin pass on an open mill. The roller temperature is adjusted to 40-60℃. Then, polyisobutylene and polyvinyl chloride are added and mixed evenly to obtain a blend.

[0021] B2. Add composite functional fillers, activators and accelerators to the blended rubber, mix evenly to obtain a two-stage compounded rubber.

[0022] B3. Add vulcanizing agent to the two-stage compound rubber, cut into thin triangular sheets, let stand at room temperature for 8-24 hours, and then vulcanize on a flat vulcanizing machine at a vulcanization temperature of 150-170℃, a pressure of 10-15MPa, and a time of 10-30 minutes to obtain medical needle-puncture resistant halogenated butyl rubber stoppers.

[0023] Furthermore, in step B1, the rolling temperature of the open mill is 40-50℃, and the mixing time is 8-12 minutes.

[0024] Furthermore, the vulcanization temperature in step B3 is 160-170℃, and the vulcanization time is 15-25min.

[0025] This invention relates to a medical-grade puncture-resistant halogenated butyl rubber stopper, primarily achieved through two aspects: formulation and vulcanization process. Halogenated butyl rubber, as the matrix material, possesses good airtightness, but its bonding with ordinary fillers is relatively weak. The addition of polyisobutylene to the formulation improves the processing flowability and flexibility of the rubber compound, reduces the hardness of the vulcanized rubber, and makes the rubber more prone to elastic deformation rather than tearing during needle puncture. The introduction of polyvinyl chloride (PVC) improves the surface strength and abrasion resistance of the stopper to some extent, reducing frictional shear damage during needle puncture. The composite functional filler is a key element; through the chemical cross-linking of its surface thiol groups with the halogenated butyl rubber during vulcanization, the filler and rubber are no longer merely physically bound, but form a strong chemical bond interface. This interfacial bonding effectively resists the tensile and shear forces generated during needle puncture, preventing the filler from easily detaching from the rubber and reducing the source of rubber debris. Simultaneously, the polyurethane elastomer microsphere core endows the filler with a certain elastic recovery capability; when the needle is withdrawn, the elastic deformation inside the rubber stopper can quickly rebound, promoting the closure of the puncture channel. The proper combination of activators and accelerators ensures a thorough vulcanization reaction, resulting in a more uniform distribution of the cross-linked network and preventing localized over-hardness or under-hardness caused by over-vulcanization or under-vulcanization. Control of vulcanization temperature and pressure ensures uniform dispersion of the filler in the rubber compound and complete chemical bonding. Overall, the puncture resistance and self-sealing performance after puncture of the rubber stopper are improved.

[0026] Compared with the prior art, the beneficial effects of the present invention are:

[0027] 1. In this invention, the thiol groups grafted onto the surface of the composite functional filler undergo a cross-linking reaction with the halogenated butyl rubber during vulcanization, forming a chemical interface bond. The bonding strength between the filler and the rubber matrix is ​​high, and the filler is not easily detached from the rubber during needle puncture, thus alleviating the problem of chipping during puncture.

[0028] 2. The composite functional filler of the present invention uses polyurethane elastomer microspheres as the core, which has a certain elastic recovery ability. After the needle is pulled out, it can push the rubber around the puncture hole to rebound and close. The self-sealing performance is significantly improved after puncture, and the risk of leakage is reduced.

[0029] 3. This invention, through the core-shell structure design and surface chemical grafting modification of the composite functional filler, enables the filler to be uniformly dispersed in the rubber matrix and the interface bonding to be stable. The rubber stopper balances low puncture force and good sealing performance under repeated puncture conditions, resulting in good overall reliability. Attached Figure Description

[0030] Figure 1 The FTIR infrared spectrum of the composite functional filler prepared in Example 1 of this invention. Detailed Implementation

[0031] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are merely some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0032] Preparation Example 1

[0033] Preparation of composite functional fillers:

[0034] 1. Components by weight:

[0035] 100 parts of polypropylene glycol, 32.5 parts of isophorone diisocyanate, 7.5 parts of dimethylolpropionic acid, 7.5 parts of triethylamine, 3 parts of ethylenediamine, 30 parts of tetraethyl orthosilicate, 11.5 parts of γ-mercaptopropyltrimethoxysilane, 15 parts of ammonia water with a mass concentration of 26.5%, 320 parts of anhydrous ethanol, and 80 parts of deionized water.

[0036] The isophorone diisocyanate was purchased from Sigma-Aldrich, catalog number 317624.

[0037] 2. Preparation method:

[0038] A1. Preparation of polyurethane elastomer microspheres: 100 parts of polypropylene glycol were added to a reactor equipped with a stirrer, thermometer, and condenser, and dehydrated for 2 hours at 110℃ and a vacuum of -0.09 MPa. The temperature was lowered to 60℃, and 32.5 parts of isophorone diisocyanate were added. The mixture was stirred at 300 rpm for 2.5 hours at 80℃ under nitrogen protection to obtain an isocyanate-terminated prepolymer. 7.5 parts of dimethylolpropionic acid were added, and the reaction was continued at 78℃ for 1.5 hours. The temperature was lowered to 40℃, and 7.5 parts of triethylamine were added, and neutralization was carried out for 30 minutes, achieving a neutralization degree of 95%. The neutralized prepolymer was dispersed in 400 parts of deionized water under high-speed stirring at 1200 rpm for 10 minutes. 3 parts of ethylenediamine were added, and chain extension was carried out at 35℃ for 2 hours to obtain a polyurethane elastomer microsphere emulsion with a solid content of 25%.

[0039] A2. Silica Shell Coating: Take 100 parts of the emulsion obtained in step A1 (based on the dry weight of the microspheres) and add it to a mixed solvent consisting of 320 parts of anhydrous ethanol and 80 parts of deionized water. Disperse the mixture by ultrasonication at 40 kHz and 300 W for 30 min. Adjust the pH to 9.5 with 15 parts of 26.5% ammonia solution, raise the temperature to 45℃, and add 30 parts of tetraethyl orthosilicate dropwise at 0.8 mL / min while stirring at 500 rpm for 1.5 h. After the addition is complete, continue the reaction at 45℃ for 5 h to obtain a silica-coated polyurethane core-shell microsphere suspension.

[0040] A3. Surface grafting modification: 11.5 parts of γ-mercaptopropyltrimethoxysilane were added to the core-shell microsphere suspension obtained in step A2, and the mixture was stirred at 55°C and 500 rpm for 4 hours. Then, the pH was adjusted to 6.5 with glacial acetic acid and the mixture was aged for another 2 hours.

[0041] A4. Post-processing: The product obtained in step A3 was centrifuged at 9000 rpm for 18 min, and the supernatant was discarded. The resulting solid was washed twice with deionized water and twice with anhydrous ethanol, centrifuged at 9000 rpm for 15 min after each wash. The washed solid was placed in a vacuum drying oven and dried at 70℃ and -0.08 MPa for 18 h. The dried block product was mechanically pulverized and passed through a 300-mesh sieve, with a sieve passing rate of not less than 98%, to obtain the composite functional filler. The thiol grafting amount of the obtained composite functional filler was 0.55 mmol / g.

[0042] like Figure 1 As shown, at approximately 3400-3500cm -1 The broad absorption peak at approximately 2960-2870 cm⁻¹ can be attributed to the stretching vibrations of NH₃, residual Si-OH, and adsorbed water in the polyurethane. -1 The absorption corresponds to the -CH2 / -CH3 stretching vibrations in the polypropylene glycol soft segment and mercaptopropyl segment; Figure 1 The relatively strong absorption peak is located at approximately 1850 cm⁻¹ on the horizontal axis. -1 This peak position is higher than the common absorption range of polyurethane urethane C=O, therefore it is not directly attributed to urethane C=O or used as a separate criterion for polyurethane core formation; 1500-1550 cm⁻¹ -1 and 1400-1450cm -1 Nearby absorption corresponds to NH bending, CN stretching, and methylene bending vibrations; 1100-1000 cm⁻¹ -1 The strong, broad peak in the region is due to the Si-O-Si asymmetric stretching vibration, which is the main characteristic peak for the formation of the silica shell, approximately 950 cm⁻¹. -1 The vicinity can be attributed to Si-OH or Si-OC related vibrations, approximately 800 cm. -1 and 700cm -1 The nearby absorption corresponds to the Si-O-Si symmetric vibration and the CS-related vibration. This is because the SH stretching vibration is typically located at approximately 2550-2600 cm⁻¹. -1 Furthermore, the absorption is relatively weak, resulting in a weak signal or shoulder peak, which is consistent with the actual situation that FTIR does not necessarily show a strong SH peak after grafting mercaptosilane onto the surface.

[0043] Preparation Example 2

[0044] The composite functional filler was prepared by referring to the preparation method in Preparation Example 1, except that the amount of tetraethyl orthosilicate was replaced from 30 parts by mass to 25 parts by mass, and the rest remained the same as in Preparation Example 1.

[0045] Preparation Example 3

[0046] The composite functional filler was prepared by referring to the preparation method in Preparation Example 1, except that the amount of γ-mercaptopropyltrimethoxysilane was replaced from 11.5 parts by mass to 10 parts by mass, and the rest remained the same as in Preparation Example 1.

[0047] Preparation Example 4

[0048] The composite functional filler was prepared by referring to the preparation method in Preparation Example 1, except that the pH of the system in the silica shell coating step was replaced with 9.0 instead of 9.5, and everything else remained the same as in Preparation Example 1.

[0049] Comparative Preparation Example 1

[0050] The composite functional filler was prepared by referring to the preparation method in Preparation Example 1, except that the polypropylene glycol was replaced with an equal mass of polytetrahydrofuran ether glycol, and everything else remained the same as in Preparation Example 1.

[0051] Comparative Preparation Example 2

[0052] The composite functional filler was prepared by referring to the preparation method in Preparation Example 1, except that the isophorone diisocyanate was replaced with an equal mass of diphenylmethane diisocyanate, and everything else remained the same as in Preparation Example 1.

[0053] Comparative preparation example 3

[0054] The composite functional filler was prepared by referring to the preparation method in Preparation Example 1, except that γ-mercaptopropyltrimethoxysilane was replaced with an equal mass of γ-aminopropyltriethoxysilane, and everything else remained the same as in Preparation Example 1.

[0055] Comparative preparation example 4

[0056] The composite functional filler was prepared by referring to the preparation method in Preparation Example 1, except that γ-mercaptopropyltrimethoxysilane was replaced with an equal mass of γ-(methacryloyloxy)propyltrimethoxysilane, and everything else remained the same as in Preparation Example 1.

[0057] Comparative preparation example 5

[0058] The composite functional filler was prepared according to the preparation method in Preparation Example 1, except that the pH of the system in the silica shell coating step was replaced with 7.0 (adjusted to pH 7.0 with ammonia water), and the rest remained the same as in Preparation Example 1.

[0059] Comparative preparation example 6

[0060] The preparation of the composite functional filler is the same as in Preparation Example 1, except that the addition method of tetraethyl orthosilicate is changed from "adding at a rate of 0.8 mL / min" to "adding rapidly in one go".

[0061] Comparative preparation example 7

[0062] The preparation of the composite functional filler is the same as in Preparation Example 1, except that the step of "adjusting the pH of the system to 6.5 with acetic acid" in the aging step after surface grafting modification is replaced with "not adjusting the pH, maintaining the pH of the system at 9.5".

[0063] Comparative Preparation Example 8

[0064] The composite functional filler was prepared according to the preparation method in Preparation Example 1. Thioyl silica particles were prepared in a mixed solvent of ethanol / water at a volume ratio of 4:1, using the same amounts of tetraethyl orthosilicate and γ-mercaptopropyltrimethoxysilane as in Preparation Example 1, as well as the same pH and temperature conditions. However, polyurethane elastomer microsphere emulsion was not added. Everything else remained the same as in Preparation Example 1.

[0065] Comparative preparation example 9

[0066] The composite functional filler was prepared according to the preparation method in Preparation Example 1. In a mixed solvent of ethanol / water at a volume ratio of 4:1, a polyurethane elastomer microsphere emulsion was prepared according to A1 in Preparation Example 1. The tetraethyl orthosilicate coating step was omitted, and γ-mercaptopropyltrimethoxysilane was directly added for treatment. Everything else was the same as in Preparation Example 1.

[0067] Comparative preparation example 10

[0068] The composite functional filler was prepared according to the preparation method in Preparation Example 1. In a mixed solvent of ethanol / water at a volume ratio of 4:1, polyurethane elastomer microspheres, precipitated silica and γ-mercaptopropyltrimethoxysilane of the same dry weight as in Preparation Example 1 were stirred and mixed in ethanol for 4 hours and then dried. No in-situ silica coating or surface grafting reaction was performed. Everything else was the same as in Preparation Example 1.

[0069] Reactivity tests of the composite functional fillers prepared in the preparation examples and comparative preparation examples:

[0070] 1. Determination of thiol grafting amount: Accurately weigh 0.5 g of filler sample, add 20 mL of N,N-dimethylformamide, and sonicate for 15 min; add 5 mL of 0.01 mol / L Ellman reagent in Tris-HCl buffer solution (pH=8.0), and shake at room temperature in the dark for 30 min; after centrifugation, take the supernatant and measure the absorbance at 412 nm. Plot a standard curve using L-cysteine ​​and calculate the thiol grafting amount. The data are shown in Table 1.

[0071] 2. Thiol Accessibility Model Reaction: Weigh 0.5 g of filler, add 30 mL of anhydrous ethanol, and ultrasonically disperse for 10 min. Then add 2.0 g of 1-bromobutane and 0.5 g of triethylamine, and stir at 60 °C under nitrogen protection for 4 h. After the reaction, centrifuge, wash, and dry. Measure the thiol content before and after the reaction, and calculate using the formula: "Thiol Consumption Rate = (Thiol Content Before Reaction - Thiol Content After Reaction) / Thiol Content Before Reaction × 100%". The data are shown in Table 1.

[0072] 3. Surface chemical stability test: The filler was subjected to Soxhlet extraction in anhydrous ethanol for 6 hours, and after drying, the S2p and Si2p peak areas were measured by X-ray photoelectron spectroscopy, and the S2p / Si2p peak area ratio retention rate was calculated. The data are shown in Table 1.

[0073] Table 1. Reactivity test data of the composite functional fillers prepared in the preparation examples and comparative preparation examples.

[0074] Note: Comparative Preparation Example 3 and Comparative Preparation Example 4 used γ-aminopropyltriethoxysilane and γ-(methacryloyloxy)propyltrimethoxysilane to replace γ-mercaptopropyltrimethoxysilane, respectively. No mercapto groups that can be effectively quantified by Ellman's reagent were introduced into the system. Therefore, the mercapto group consumption rate and S2p / Si2p peak area ratio retention rate after the 1-bromobutane model reaction have no basis for calculation and are indicated as "not applicable" in the table.

[0075] As shown in Table 1, the thiol grafting amount, thiol accessibility, and surface chemical stability of the composite functional fillers in Examples 1-4 are all within a reasonable range, indicating that a relatively stable soft-core-hard-shell-reactive interface structure is formed between the polyurethane elastomer microspheres, the in-situ silica shell, and γ-mercaptopropyltrimethoxysilane. The polyurethane core provides a foundation for elastic recovery, the silica shell provides inorganic reinforcement and a certain barrier effect, and provides a reactive surface for the silane coupling reaction, while the thiol silane improves the interfacial compatibility between the filler and the halogenated butyl rubber and the subsequent vulcanization bonding ability. In the comparative preparation examples, changing the type of polyurethane soft segment or isocyanate affects the surface state of the microspheres and the uniformity of shell deposition; coupling agents without thiol groups cannot provide effective active sites for reaction with halogenated butyl rubber; improper control of coating pH, tetraethyl orthosilicate addition method, or post-grafting pH can lead to a decrease in shell continuity, thiol exposure, and surface stability; omitting the polyurethane core, in-situ silica coating, or surface grafting reaction weakens the dispersion stability, interfacial bonding, and structural reinforcement of the filler. The above data support the technical effect of the composite functional filler of this invention in improving the needle-puncture resistance and self-sealing performance of subsequent rubber stoppers through component synergy, core-shell structure interaction, and interfacial chemical bonding.

[0076] Example 1

[0077] Preparation of a medical needle-puncture resistant halogenated butyl rubber stopper:

[0078] 1. Raw material components by weight:

[0079] Halogenated butyl rubber: 100 parts, chlorinated butyl rubber is selected.

[0080] Polyisobutylene: 12 parts.

[0081] Polyvinyl chloride: 10 parts.

[0082] Composite functional packing material: 20 parts. The composite functional packing material prepared in Preparation Example 1 was used.

[0083] Vulcanizing agent: 3 parts. Magnesium oxide is preferred.

[0084] Accelerator: 1.2 parts, tetramethylthiuram disulfide is selected.

[0085] Surfactant: 2 parts, stearic acid is preferred.

[0086] The chlorinated butyl rubber was purchased from Shanghai Yongzheng Chemical Co., Ltd.

[0087] The tetramethylthiuram disulfide was purchased from Supelcu, catalog number: 45689.

[0088] 2. Preparation method:

[0089] B1. Adjust the rolling temperature of the open mill to 45℃ and the rolling gap to 1.0mm. Add 100 parts of chlorinated butyl rubber and plasticize it three times in thin passes, folding and rolling it after each thin pass. Then add 12 parts of polyisobutylene and 10 parts of polyvinyl chloride in sequence, and mix at 45℃ for 10 minutes. During this period, alternately cut and re-mix the rubber every 3 minutes to obtain the blended rubber.

[0090] B2. Keep the roller temperature at 45℃, add 20 parts of composite functional filler, 2 parts of stearic acid and 1.2 parts of tetramethylthiuram disulfide to the blended rubber in sequence, mix for 8 minutes, and make triangular wraps 6 times to make the filler and additives evenly dispersed in the rubber matrix to obtain the two-stage compound.

[0091] B3. Add 3 parts magnesium oxide to the second-stage compound rubber, continue mixing for 5 minutes, pass through a thin pass and make triangular wraps 6 times before cutting the film. The film thickness should be controlled at 3.0 mm. Let the film stand at 23±2℃ for 16 hours.

[0092] B4. Place the rested film into a 20mm injection bottle stopper mold, and vulcanize it at 160℃, 12MPa, and 20min. After opening the mold and removing the flash, the stopper blank is obtained. The thickness of the stopper crown is 2.8mm, and the thickness of the puncture area is 3.2mm.

[0093] B5. Post-processing: Wash the rubber stopper blank with purified water at 70℃ three times for 30 minutes each time, dry it with hot air circulation at 85℃ for 3 hours, and then sterilize it with moist heat at 121℃ for 30 minutes to obtain medical needle-puncture resistant halogenated butyl rubber stopper.

[0094] Examples 2-4

[0095] The preparation of a medical needle-resistant halogenated butyl rubber stopper is carried out by referring to the preparation method in Example 1, except that the composite functional filler is replaced with the composite functional filler prepared in Preparation Examples 2-4 in sequence, and the rest is the same as in Example 1.

[0096] Example 5

[0097] The preparation of a medical needle-resistant halogenated butyl rubber stopper is carried out by referring to the preparation method in Example 1, except that the amount of composite functional filler is adjusted from 20 parts to 18 parts, and the rest is the same as in Example 1.

[0098] Example 6

[0099] The preparation of a medical needle-resistant halogenated butyl rubber stopper is carried out by referring to the preparation method in Example 1, except that the amount of polyisobutylene is adjusted from 12 parts to 10 parts, and the rest is the same as in Example 1.

[0100] Comparative Examples 1-10

[0101] The preparation of a medical needle-resistant halogenated butyl rubber stopper is carried out by referring to the preparation method in Example 1, except that the composite functional filler is replaced in turn with the composite functional filler prepared in Comparative Preparation Examples 1-10, and the rest is the same as in Example 1.

[0102] Comparative Example 11

[0103] The preparation of a medical needle-puncture resistant halogenated butyl rubber stopper is carried out by referring to the preparation method in Example 1, except that the composite functional filler is replaced with an equal mass of precipitated silica, and the rest is the same as in Example 1.

[0104] Comparative Example 12

[0105] The preparation of a medical needle-resistant halogenated butyl rubber stopper is carried out by referring to the preparation method in Example 1, except that the polyisobutylene is replaced with an equal mass of liquid paraffin, and the rest is the same as in Example 1.

[0106] Comparative Example 13

[0107] The preparation of a medical needle-resistant halogenated butyl rubber stopper is carried out by referring to the preparation method in Example 1, except that the halogenated butyl rubber is replaced with an equal mass of unhalogenated butyl rubber, and the rest is the same as in Example 1.

[0108] Performance testing:

[0109] 1. Quantitative Test of Puncture Debris: The puncture method was followed according to the General Chapter of Part IV of the 2020 edition of the Chinese Pharmacopoeia for the Examination of Puncture Debris from Rubber Stoppers and Gaskets for Injection, with the addition of microscopic counting. A 25G injection needle conforming to GB 15811 was used to vertically puncture the simulated puncture area of ​​the rubber stopper at a speed of 70-80 times / min, with a puncture depth of not less than 6 mm. Each rubber stopper was punctured 50 times consecutively. After puncture, the puncture area was rinsed with a specified volume of purified water, and the rinsing fluid was collected, filtered through a filter membrane, and the number of rubber debris with a particle size of not less than 50 μm was counted under a microscope. The data are shown in Table 2.

[0110] 2. Self-sealing performance test after puncture: After 50 consecutive punctures in the same simulated puncture area, the needle was removed and allowed to stand for 10 seconds. Then, a rubber stopper was fitted onto a matching glass bottle containing 80% of the labeled volume of purified water and capped. The bottle was then inverted and placed in a vacuum desiccator containing 0.1% methylene blue solution. A vacuum was drawn to an absolute pressure of 25 kPa and maintained for 30 minutes. After returning to normal pressure, the pressure was maintained for another 30 minutes, and the solution inside the bottle was observed to see if it turned blue. The data are shown in Table 2.

[0111] 3. Puncture force performance test: Referring to the puncture force test method for rubber stoppers and gaskets for injection in YBB00332004-2015, a universal testing machine and a 25G standard injection needle were used to vertically puncture the rubber stopper at a speed of 200 mm / min, and the maximum peak force was recorded. The data are shown in Table 2.

[0112] 4. Tensile strength test: Referring to GB / T 528-2009, the same batch of vulcanized rubber sheets were cut into type 2 dumbbell specimens, and the tensile strength at break was tested at a speed of 500 mm / min. The data are shown in Table 2.

[0113] 5. Preliminary safety test of water extraction: Referring to the preparation method of rubber stopper extract in the General Chapter of Part IV of the 2020 edition of the Chinese Pharmacopoeia, rubber stopper samples prepared in each example and comparative example were ultrasonically washed three times with purified water and then air-dried at room temperature. The ratio of the total surface area of ​​the rubber stopper to the volume of purified water was 1 cm³. 2 A 2 mL sample was used to immerse the rubber stopper in purified water and extract it at 121°C for 30 minutes in an autoclave. After cooling, the extract was collected for testing. The appearance of the extract was visually observed to determine whether it was clear, colorless, or had any opalescence or oiliness. The pH difference between the extract and the blank purified water was determined according to the method in General Chapter 0631 of the Chinese Pharmacopoeia. The ultraviolet absorbance was scanned using a UV-Vis spectrophotometer in the wavelength range of 220-360 nm, and the maximum absorbance value was recorded. The non-volatile matter was determined according to the method in General Chapter 0831 of the Chinese Pharmacopoeia. 50 mL of the extract was evaporated and dried to constant weight, and the weight of the residue was calculated (in mg / 100 mL). This test is used to illustrate the preliminary evaluation of the suitability of the medical packaging of the example samples. For specific registration applications, full-item validation should still be completed according to the applicable pharmaceutical packaging material standards and drug compatibility requirements. The data are shown in Table 3.

[0114] Table 2. Puncture and mechanical property test data of medical needle-resistant halogenated butyl rubber stoppers prepared in the examples and comparative examples.

[0115] Example 1 1.8 20 / 20 100 3.2 12.8 Example 2 2.4 20 / 20 100 3.3 12.3 Example 3 2.8 19 / 20 95 3.4 12.1 Example 4 3.1 19 / 20 95 3.5 11.8 Example 5 3.4 19 / 20 95 3.1 11.6 Example 6 3.2 19 / 20 95 3.6 12.5 Comparative Example 1 4.9 18 / 20 90 3.7 10.9 Comparative Example 2 5.4 17 / 20 85 4.2 10.6 Comparative Example 3 7.8 15 / 20 75 4.6 9.6 Comparative Example 4 7.1 16 / 20 80 4.4 9.9 Comparative Example 5 9.3 14 / 20 70 4.8 9.1 Comparative Example 6 8.6 14 / 20 70 4.9 9.4 Comparative Example 7 7.5 15 / 20 75 4.3 10 Comparative Example 8 6.8 15 / 20 75 5 10.4 Comparative Example 9 10.6 12 / 20 60 3.8 8.5 Comparative Example 10 11.4 11 / 20 55 5.2 8.2 Comparative Example 11 10.1 13 / 20 65 5.1 9 Comparative Example 12 8.1 14 / 20 70 3 8.6 Comparative Example 13 8.8 14 / 20 70 3.6 9.2

[0116] Table 3. Preliminary safety test data of water immersion extract of medical needle-puncture resistant halogenated butyl rubber stoppers prepared in the examples and comparative examples.

[0117] Example 1 Clear, colorless 0.18 0.034 0.9 Example 2 Clear, colorless 0.21 0.038 1 Example 3 Clear, colorless 0.23 0.041 1.1 Example 4 Clear, colorless 0.26 0.045 1.2 Example 5 Clear, colorless 0.2 0.037 1 Example 6 Clear, colorless 0.22 0.039 1.1 Comparative Example 1 Clear, colorless 0.31 0.054 1.5 Comparative Example 2 Clear, slightly yellow 0.36 0.061 1.7 Comparative Example 3 Clear, colorless 0.52 0.083 2.2 Comparative Example 4 Clear, colorless 0.44 0.074 2 Comparative Example 5 Clear, slightly opalescent 0.61 0.096 2.7 Comparative Example 6 Clear, slightly opalescent 0.58 0.09 2.5 Comparative Example 7 Clear, colorless 0.66 0.088 2.4 Comparative Example 8 Clear, colorless 0.42 0.071 2 Comparative Example 9 Clear, slightly opalescent 0.74 0.112 3.2 Comparative Example 10 Clear, slightly opalescent 0.82 0.126 3.5 Comparative Example 11 Clear, colorless 0.5 0.079 2.3 Comparative Example 12 Clear, with slight oily residue on the surface 0.46 0.138 4.1 Comparative Example 13 Clear, colorless 0.43 0.07 2

[0118] Tables 2 and 3 show that the examples are superior to the comparative examples in terms of puncture debris control, post-puncture channel closure, self-sealing, mechanical strength, and water extraction stability. This indicates that the soft core-hard shell-reactive interface structure of the composite functional filler can play a synergistic role: the polyurethane elastomer microsphere core provides local elastic buffering and recovery during needle insertion and withdrawal, reducing stress concentration and pore wall tearing in the rubber matrix; the silica shell improves the filler's rigidity, dispersion stability, and interfacial load-bearing capacity, preventing significant debonding or pull-out of the filler during mixing, vulcanization, and needle shearing; the surface thiol groups form chemical interfacial bonds with halogenated butyl rubber during vulcanization, enabling the filler to participate in cross-linking network construction rather than relying solely on physical embedding, thereby improving interfacial compatibility, stress transmission, and cross-linking uniformity. In contrast, the comparative example, due to changes in the polyurethane soft segment, isocyanate type, coupling agent type, coating pH, tetraethyl orthosilicate addition method, post-grafting pH control, or omission of key structural units such as the soft core, in-situ silica coating, and surface grafting, resulted in decreased shell continuity, mercapto accessibility, filler dispersibility, and interfacial bonding strength. This made it more prone to interfacial delamination, irreversible pore deformation, and debris shedding during needle puncture. Simultaneously, interfacial instability or migration of low-molecular-weight components increased the amount of migratable substances and non-volatile residues in the extract, leading to deterioration in appearance, pH changes, UV absorption, and non-volatile matter content. Therefore, the data trends in Tables 2 and 3 can be explained by component synergy, core-shell structure effects, interfacial compatibility, dispersion stability, barrier effects, thermal vulcanization crosslinking effects, and elasticity enhancement effects, which are basically consistent with the technical mechanism of the needle-resistant halogenated butyl rubber stopper of this invention.

[0119] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A medical-grade puncture-resistant halogenated butyl rubber stopper, characterized in that, It is composed of the following components in parts by weight: 100 parts of halogenated butyl rubber, 5-20 parts of polyisobutylene, 5-15 parts of polyvinyl chloride, 10-30 parts of composite functional filler, 2-5 parts of vulcanizing agent, 0.5-2 parts of accelerator, and 1-3 parts of activator. The composite functional filler has a core-shell structure, with polyurethane elastomer microspheres as the core. The polyurethane elastomer microspheres are made by reacting polypropylene glycol, isophorone diisocyanate, dimethylolpropionic acid, triethylamine and ethylenediamine with a number average molecular weight of 1000-3000. The core is coated with a continuous silica shell. The surface of the silica shell is chemically bonded with γ-mercaptopropyltrimethoxysilane through silicon-oxygen bonds, and the amount of thiol grafting is 0.42-0.60 mmol / g. The thiol consumption rate of the composite functional filler after reacting with the 1-bromobutane model is not less than 85%.

2. The medical needle-puncture-resistant halogenated butyl rubber stopper according to claim 1, characterized in that, The composite functional filler is prepared from the following raw materials by weight through a multi-step reaction: 100 parts of polypropylene glycol with a number average molecular weight of 1000-3000, 30-35 parts of isophorone diisocyanate, 5-10 parts of dimethylolpropionic acid, 5-10 parts of triethylamine, 1-5 parts of ethylenediamine, 25-35 parts of tetraethyl orthosilicate, 10-12 parts of γ-mercaptopropyltrimethoxysilane, 12-18 parts of ammonia water with a mass concentration of 25%-28%, 300-350 parts of anhydrous ethanol, and 80-100 parts of deionized water.

3. A medical needle-puncture-resistant halogenated butyl rubber stopper according to claim 1 or 2, characterized in that, X-ray photoelectron spectroscopy revealed that the composite functional filler surface contained S2p and Si2p signals, and after Soxhlet extraction with anhydrous ethanol for 6 hours, the S2p / Si2p peak area ratio retention rate was not less than 85%.

4. A medical puncture-resistant halogenated butyl rubber stopper according to claim 1 or 2, characterized in that, The preparation method of the composite functional filler includes the following steps: A1. Preparation of polyurethane elastomer microspheres: Polypropylene glycol is vacuum dehydrated at 100-120℃, cooled to 60℃, isophorone diisocyanate is added, and the mixture is stirred at 75-85℃ for 2-3 hours to obtain an isocyanate-terminated prepolymer; dimethylolpropionic acid is added, and the mixture is further reacted at 75-80℃ for 1-2 hours, cooled to 40℃, and triethylamine is added for neutralization, with a neutralization degree of 90%-100%; the neutralized prepolymer is dispersed in deionized water under high-speed stirring at 1000-1500 rpm, and then ethylenediamine is added for post-chain extension, controlling the solid content to 20%-30%, to obtain a polyurethane elastomer microsphere emulsion; A2. Silica shell coating: Take 100 parts of the polyurethane elastomer microsphere emulsion obtained in step A1, based on the dry weight of the microspheres, and add it to a mixed solvent composed of anhydrous ethanol and deionized water in a volume ratio of 4:

1. Disperse the mixture ultrasonically at a power of 200-500W, a frequency of 40kHz, and a time of 15-30min. Adjust the pH of the system to 9-10 with the ammonia water, raise the temperature to 40-50℃, and add the tetraethyl orthosilicate dropwise at a rate of 0.5-1.0mL / min under stirring for 1-2h. After the addition is complete, continue stirring and reacting for 4-6h to obtain a core-shell microsphere suspension of polyurethane coated with silica. A3. Surface grafting modification: Add the γ-mercaptopropyltrimethoxysilane to the core-shell microsphere suspension obtained in step A2, stir and react at 50-60℃ for 3-5h, then adjust the pH of the system to 6-7 with glacial acetic acid, and continue aging for 2h. A4. Post-processing: Centrifuge the product obtained in step A3 at 8000-10000 rpm for 15-20 min, discard the supernatant, wash the solid alternately with deionized water and anhydrous ethanol, vacuum dry at 60-80℃ for 12-24 h, mechanically pulverize and pass through a 300-mesh sieve to obtain the composite functional filler.

5. A medical puncture-resistant halogenated butyl rubber stopper according to claim 1, characterized in that, The halogenated butyl rubber is either chlorinated butyl rubber or brominated butyl rubber.

6. A medical puncture-resistant halogenated butyl rubber stopper according to claim 1, characterized in that, The vulcanizing agent is selected from one or more of magnesium oxide and sulfur.

7. A medical needle-puncture-resistant halogenated butyl rubber stopper according to claim 1, characterized in that, The accelerator is selected from one or more of tetramethylthiuram disulfide, zinc diethyldithiocarbamate, and 2-mercaptobenzothiazole. The active agent is stearic acid.

8. A vulcanization preparation process for a medical needle-puncture-resistant halogenated butyl rubber stopper as described in any one of claims 1-7, characterized in that, Includes the following steps: B1. The halogenated butyl rubber is plasticized in a thin pass on a two-roll mill, the roller temperature is adjusted to 40-60℃, and then the polyisobutylene and polyvinyl chloride are added and mixed evenly to obtain a blended rubber. B2. Add the composite functional filler, activator and accelerator to the blended rubber, mix evenly to obtain a two-stage compounded rubber; B3. Add the vulcanizing agent to the two-stage compound rubber, cut the thin-walled triangular sheet, let it stand at room temperature for 8-24 hours, and then vulcanize it on a flat vulcanizing machine at a vulcanizing temperature of 150-170℃, a pressure of 10-15MPa, and a time of 10-30 minutes to obtain a medical needle-puncture resistant halogenated butyl rubber stopper.

9. The vulcanization preparation process of a medical needle-puncture-resistant halogenated butyl rubber stopper according to claim 8, characterized in that, In step B1, the rolling temperature of the open mill is 40-50℃, and the mixing time is 8-12 minutes.

10. The vulcanization preparation process of a medical needle-puncture-resistant halogenated butyl rubber stopper according to claim 8, characterized in that, The vulcanization temperature in step B3 is 160-170℃, and the vulcanization time is 15-25min.